Transformasi lembaga medis di Hindia Belanda: potret sejarah kesehatan di Indonesia dalam perspektif politik (1850-1942) - Rendy Kurniawan; Rahmawati Agustia (Historiography: Journal of Indonesian History and Education, 2021)
This article will portray a journey of the history of health in Indonesia in the Dutch colonialism period within an institutional perspective. The history of medical institute in the Dutch Indies period seems to be interesting to be elaborated within the spectrum of the history of health in Indonesia. This is because the fact that politics also involves to play its roles in the development of the history and dynamics of the medical institute in Indonesia which is initially pioneered by military medical organization known as Militair Geneeskundige Dienst. Then, in the following period, the medical institution in the Dutch Indies get separated into military and public healthcare which popularly known as Burgerlijk Geneeskundige Dienst. Based on these explanations, by applying four methodologies of historical research, they are; 1) Heuristics, 2)Critics, 3)Interpretation, 4) Historiography, this research is going to try to reveal a number of interesting discourses concerning the history of medical institution in the Dutch Indies Colonialism, which involve the transformation of medical institution in the Dutch Indies, policies that concerning with the healthcare and important figures in the history of health in the colonial time.Karya tulis ini akan memotret perjalanan sejarah kesehatan di Indonesia pada masa penjajahan Belanda dalam perspektif kelembagaan. Sejarah lembaga medis pada masa Hindia Belanda nampaknya cukup menarik untuk dibahas dalam spektrum sejarah kesehatan di Indonesia. Hal ini berkaitan erat dengan fakta bahwa politik juga memainkan peranan penting dalam perkembangan sejarah dan dinamika lembaga medis di Indonesia pada masa kolonial yang diawali oleh lembaga kesehatan khusus bagi militer dan dikenal dengan Militair Geneeskundige Dienst. Lalu, dalam perjalanan sejarahnya, lembaga medis pada masa Hindia Belanda terdiferensiasi menjadi lembaga medis militer dan publik atau Burgerlijk Geneeskundige Dienst. Berdasarkan hal tersebut, dengan memanfaatkan empat metodologi sejarah, yaitu; 1) Heuristik, 2) Kritik, 3) Interpretasi dan 4) Historiografi, kajian ini akan coba mengungkap beberapa hal menarik terkait sejarah lembaga medis di masa Hindia Belanda, di antaranya adalah transformasi lembaga medis, kebijakan-kebijakan yang berkaitan erat dengan diskursus kesehatan dan tokoh-tokoh penting dalam sejarah kesehatan pada masa kolonial.